2022
DOI: 10.1039/d2tb01385a
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting polymer dots as fluorescent probes forin vitrobiosensing

Abstract: Semiconducting polymer dots (Pdots) have emerged as novel fluorescent probes with excellent characteristics, such as ultrahigh molar extinction coefficient, easy tunable absorption and emission bands, high brightness, and excellent photostability....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 104 publications
0
22
0
Order By: Relevance
“…Some prestigious reviews have demonstrated detailed applications of CPNPs, mainly for biofields or organic photovoltaics (OPVs). In this work, we comprehensively review both electronics and bioapplications and focus on parameters arising from synthetic procedures which have significant effects on each application. We first introduce particle formation mechanisms, followed by the synthesis methods corresponding to those mechanisms with detailed steps, characteristics, and size parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Some prestigious reviews have demonstrated detailed applications of CPNPs, mainly for biofields or organic photovoltaics (OPVs). In this work, we comprehensively review both electronics and bioapplications and focus on parameters arising from synthetic procedures which have significant effects on each application. We first introduce particle formation mechanisms, followed by the synthesis methods corresponding to those mechanisms with detailed steps, characteristics, and size parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, semiconducting polymer dots (Pdots) have attracted extensive attention for in vivo fluorescence imaging applications [ 24 ]. Pdots are types of organic polymer-based nanoparticles, mainly composed of π-conjugated hydrophobic polymer as light absorber and fluorescent emitter [ 25 ], with additional non-conjugated polyethylene glycol (PEG)-based amphiphilic polymers as a surfactant to stabilize the nanoparticles in aqueous solution and to avoid non-specific binding of Pdots to biological species [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pdots are types of organic polymer-based nanoparticles, mainly composed of π-conjugated hydrophobic polymer as light absorber and fluorescent emitter [ 25 ], with additional non-conjugated polyethylene glycol (PEG)-based amphiphilic polymers as a surfactant to stabilize the nanoparticles in aqueous solution and to avoid non-specific binding of Pdots to biological species [ 26 ]. Pdots can be prepared by nanoprecipitation, mini-emulsion polymerization, self-assembly of amphiphilic block copolymers, or a microfluidic approach, which are detailed in previous reviews [ 24 , 27 , 28 ]. Usually, the mass or volume fraction of the conjugated polymer in a single Pdot must be greater than 50% and with a diameter less than 40 nm [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of biosensing devices that can monitor environmental and dietary hazards has grabbed much attention in recent years [ 1 , 2 ]. In particular, fluorescent biosensors based on bio-conjugated nanomaterials and involving a Förster resonance energy transfer (FRET) mechanism have great advantages in term of sensitivity and simple operating procedures [ 3 ]. The choice of materials used to develop fluorescent biosensors is very crucial because surface charge, electron transport behavior and structural and optical properties decide the ability of materials to perform selective, sensitive and reliable detection [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, fluorescent biosensors based on bio-conjugated nanomaterials and involving a Förster resonance energy transfer (FRET) mechanism have great advantages in term of sensitivity and simple operating procedures [ 3 ]. The choice of materials used to develop fluorescent biosensors is very crucial because surface charge, electron transport behavior and structural and optical properties decide the ability of materials to perform selective, sensitive and reliable detection [ 3 ]. Thus, there is a dire need of such materials in which controlling their synthesis parameters can induce different properties and functionalities such as surface charge and morphology.…”
Section: Introductionmentioning
confidence: 99%